Metal organic framework against chemical warfare agents in gas adsorption - Chia, Chan Wing (2019)
Metal Organic Frameworks (MOFs) are a class of porous materials with highly desirable properties that enabled these materials to deliver excellent results to a wide range of application such as gas storage, gas capture, and catalysis. These properties make MOFs a potential alternative to be deployed as an active adsorbent and decontaminant against chemical warfare agents rather than the conventional approach of using activated carbon.